ANALYSIS OF INTEREST RATE INFLUENCE ON MONETARY POLICY IN INDONESIA - Purwanto, Fajar (Program Doktor Ilmu Ekonomi, 2022)
The monetary policy of a country is influenced by the economic policies of other countries. therefore many factors influence monetary policy in a country. one factor is the value of interest rates in the country. Interest rates also affect the inflation that will occur. This certainly affects the state of the country's economy, especially Indonesia. This study aims to determine the effect of interest rate factors on monetary policy in Indonesia. The method used in this research is to conduct a meta-analysis of three journals regarding monetary policy in Indonesia. From the analysis, it is found that the interest rate has an effect on inflation and will affect monetary policy in Indonesia. In the formation of bank interest rates, the element of inflation expectations is still considered small. Meanwhile, other factors are still bigger, such as: condition of banking liquidity, less efficient banking management, bank segmentation. The use of interest rates as an indicator of inflation expectations is in line with the need for an instrument that can effectively explain the phenomenon of inflationary movements as the ultimate target for monetary policy. Keywords: interest rate, inflation, monetary policy